Performance evaluation of a HMA pavement longitudinal joint containing a void reducing asphalt membrane (VRAM) - Kamau, Joyce; Podolsky, Joseph; Williams, R. Christopher (Frontiers in Materials, 2023)
Longitudinal joint cracking in Hot Mix Asphalt (HMA) pavement is a major issue that occurs because high density (low air voids) is not easily achievable during construction as compared to the mat away from the joints. High air voids allow water infiltration, which results in moisture-induced damage to the pavement and reduced pavement service life. The use of a Void Reducing Asphalt Membrane (VRAM) has been recommended and used at longitudinal joints of asphalt pavements as a preventative treatment to achieve good performance and increase density/reduce air voids content at the longitudinal joint. The VRAM material is sprayed on top of a tack coat at the longitudinal joint 9 inches to each side of the joint below the HMA surface overlay and is believed to migrate upwards into the HMA overlay, filling 50-70% of the air voids. This study evaluated and compared the performance of longitudinal joints constructed with VRAM to that of a joint without VRAM (control). Field cores were collected from 1) a section containing VRAM and 2) a section without VRAM paved for this research. Falling head permeability was carried out to determine the permeability coefficient of the specimen. Disk Compact Tension (DCT) and Semi-Circular Bend (SCB) tests were used to evaluate cracking performance at low temperatures. At the same time, a push-pull test was used to evaluate improvement in adhesion between the top and bottom HMA layers at the intermediate temperature. The VRAM-containing samples show high values of fracture energy (Gf) and surface and joint bond energies, as compared to the control sections. A high surface and joint bond energy indicate that the longitudinal cracking at the joints will be delayed as more energy is required to initiate cracks. Additionally, VRAM-containing samples have a lower permeability coefficient compared to the control section. This indicates that the VRAM decreases the possibility of water infiltration. The elastomeric polymer in the VRAM increases the cohesion in the mixture increasing resistance to deformation and enhancing the bond strength of the joint. Additionally, the VRAM enhances the elasticity of the binder thus increasing the cracking resistance at the joint.